Leviticus in Practice - W., Rogerson, John (Practice Interpretation, 2014)
Practice Interpretation takes the everyday social conditions of people as they are described in the Bible and looks at emerging issues that confront interpreters in daily life. The latest volume in the Practice Interpretation series deals with a much-neglected but fascinating part of the Bible, the book of Leviticus. The book opens with an introduction by J.W. Rogerson. Philip Davies attempts to uncover the main theme of Leviticus, Numbers and Deuteronomy, concluding that the portrait of the ideal Israel in each gives the perspective respectively of a priest, a military commander and a lawyer. In his second essay he explores the enigmatic figure of Azazel in the atonement ritual of Leviticus 16. What parallels are there with the New Testament account of the Passion of Jesus? John Rogerson studies the term niddah in relation to the menstruating woman in Leviticus 15, concluding that we must revise our ideas and practice about impurity in the Old Testament. His second study, of the sources and compilation of Leviticus 19, suggests that we must revise our ideas and practice about holiness. John Vincent deals with the relationship between the Jubilee legislation in Leviticus and the ministry of Jesus, drawing conclusions for the nature of Christian discipleship today. Noel Irwin looks at Leviticus 19 in relation to John Wesley's view of practical holiness and his interest in the Letter of James. John Davies views Leviticus 25 from the point of view of his experience of working in apartheid South Africa.